Pink slime eaudiobook A novel. - Trías, Fernanda (Simon & Schuster Audio, 2024)
Longlisted for the NATIONAL BOOK AWARD for Translated Literature Named a BEST BOOK of 2024 by NPR, Esquire , Publishers Weekly , and ScreenRant "The disconcerting familiarity of this strange, windswept world will haunt you." — Esquire A hair-raising, poetic novel about a woman and the people who depend on her as the world around them edges toward apocalypse. In a city ravaged by a mysterious plague, a woman tries to understand why her world is falling apart. An algae bloom has poisoned the previously pristine air that blows in from the sea. Inland, a secretive corporation churns out the only food anyone can afford—a revolting pink paste, made of an unknown substance. In the short, desperate breaks between deadly windstorms, our narrator stubbornly tends to her few remaining relationships: with her difficult but vulnerable mother; with the ex-husband for whom she still harbors feelings; with the boy she nannies, whose parents sent him away even as terrible threats loomed. Yet as conditions outside deteriorate further, her commitment to remaining in place only grows—even if staying means being left behind. An evocative elegy for a safe, clean world, Pink Slime is buoyed by humor and its narrator's resiliency. This vivid and unforgettable novel explores the place where love, responsibility, and self-preservation converge.